Level of education as a risk factor for extensive prevalence of cervical intervertebral disc degenerative changes and chronic neck pain - Markotić, Vedran; Zubac, Damir; Miljko, Miro; Šimić, Goran; Zalihić, Amra; Bogdan, Gojko; Radančević, Dorijan; Šimić, Ana Dugandžić; Mašković, Josip (Central European Journal of Public Health, 2017)
OBJECTIVE: The aim of this study was to document the prevalence of degenerative intervertebral disc changes in the patients who previously reported symptoms of neck pain and to determine the influence of education level on degenerative intervertebral disc changes and subsequent chronic neck pain. METHODS: One hundred and twelve patients were randomly selected from the University Hospital in Mostar, Bosna and Herzegovina, (aged 48.5±12.7 years) and submitted to magnetic resonance imaging (MRI) of the cervical spine. MRI of 3.0 T (Siemens, Skyrim, Erlangen, Germany) was used to obtain cervical spine images. Patients were separated into two groups based on their education level: low education level (LLE) and high education level (HLE). Pfirrmann classification was used to document intervertebral disc degeneration, while self-reported chronic neck pain was evaluated using the previously validated Oswestry questionnaire. RESULTS: The entire logistic regression model containing all predictors was statistically significant, (χ2(3)=12.2, p=0.02), and was able to distinguish between respondents who had chronic neck pain and vice versa. The model explained between 10.0% (Cox-Snell R2) and 13.8% (Nagelkerke R2) of common variance with Pfirrmann classification, and it had the strength to discriminate and correctly classify 69.6% of patients. The probability of a patient being classified in the high or low group of degenerative disc changes according to the Pfirrmann scale was associated with the education level (Wald test: 5.5, p=0.02). Based on the Pfirrmann assessment scale, the HLE group was significantly different from the LLE group in the degree of degenerative changes of the cervical intervertebral discs (U=1,077.5, p=0.001). CONCLUSION: A moderate level of intervertebral disc degenerative changes (grade II and III) was equally matched among all patients, while the overall results suggest a higher level of education as a risk factor leading to cervical disc degenerative changes, regardless of age differences among respondents.
Keywords: Comorbidity; Bosna a Hercegovina; Male; Risk Factors; bolest krku; magnetická rezonanční tomografie; chronická bolest; degenerace meziobratlové ploténky; Bosnia and Herzegovina; prevalence; mužské pohlaví; Chronic Pain; Neck Pain; Intervertebral Disc; stupeň vzdělání; komorbidita; lidé; ženské pohlaví; Educational Status; Humans; rizikové faktory; Prevalence; meziobratlová ploténka; Intervertebral Disc Degeneration; Magnetic Resonance Imaging; Female; lidé středního věku; Middle Aged